Empires of belief : why we need more scepticism and doubt in the twenty-first century - Sim, Stuart (Edinburgh University Press, 2006)
"Challenges all forms of fundamentalism and unexamined belief systems from a philosophical and sceptical viewpoint." Is unquestioning belief making a global comeback? The growth of religious fundamentalism seems to suggest so. For the sceptically minded, this is a deeply worrying trend, not just confined to religion. Political, economic, and scientific theories can demand the same unquestioning obedience from the general public. Stuart Sim outlines the history of scepticism in both the Western and Islamic cultural traditions, and from the Enlightenment to postmodernism. Setting out what a sceptical politics might be like, Empires of Belief argues that we need less belief and more doubt: an engaged scepticism to replace the pervasive dogmatism that threatens our democracies. Key Features:. New book from the author of the highly successful Fundamentalist World Questions belief systems, including science and technology Intervenes in current debates around terrorism and fundamentalism Explores sceptical thought within different cultural traditions, especially Islam Suggests that scepticism can play a greater role in public and political life